Mangrove Management Strategy as a Conservation Effort in Coastal Tarakan City - Lukman, Lukman; Sodikin, Sodikin; Munawir, Abdillah (Universitas Ibn Khaldun Bogor, 2024)
One of the important components in the mangrove ecosystem is the mangrove forest. Mangrove forests consist of various types of woody and leafy trees. Parts of the roots, stems, leaves, and fruit can be utilised. The existence of mangroves certainly has a positive impact on the ecosystem and the survival of the community around the mangrove area, some of the main benefits of mangroves such as: preventing coastal erosion, protection of marine habitat and fisheries, a source of fodder for livestock and other animals, preventing global warming, the existence of mangrove ecosystems become a source of income for fishermen on the coast, as well as several other benefits that certainly greatly support the sustainability of marine habitat and development and economic development of the community. Mangroves also have a role as a source of nutrients that affect the structure, function, and balance of nutrients in an ecosystem. In addition to acting as a habitat for living things, mangrove forests also have great benefits and have the potential to improve the economic level of coastal communities. These benefits are obtained from renewable natural resources such as fish, shrimp and other economic biota; sources of firewood and processed food; and can be an educational and tourist area. The research method where the type of research used is descriptive qualitative, the source of information is the agency and the parties directly involved in managing mangroves, both organisations, self-help and local communities. Analysis using SWOT and AHP. The results showed that the strengths and weaknesses in management support each other, because the strengths in management are effective enough to compensate for the weaknesses that have not been pursued by the local government. The opportunities are good enough to be able to improve management to continue to be developed, but on the one hand threats remain which of course can encourage weak management of mangrove areas in Tarakan City. While based on AHP analysis that the most important mangrove management is improved is to involve human resources efficiently because it is a more dominant factor that needs to be applied so that the management of mangrove areas in Tarakan city can be more effective.